Research Progress in Pharmacological Activities and Applications of Cardiotonic Steroids - Ren, Junwei; Gao, Xinyuan; Guo, Xi; Wang, Ning; Wang, Xin (Frontiers in Pharmacology, 2022)
Cardiotonic steroids (CTS) are a group of compounds existing in animals and plants. CTS are commonly referred to cardiac glycosides (CGs) which are composed of sugar residues, unsaturated lactone rings and steroid cores. Their traditional mechanism of action is to inhibit sodium-potassium ATPase to strengthen the heart and regulate heart rate, so it is currently widely used in the treatment of cardiovascular diseases such as heart failure and tachyarrhythmia. It is worth noticing that recent studies have found an avalanche of inestimable values of CTS applications in many fields such as anti-tumor, anti-virus, neuroprotection, and immune regulation through multi-molecular mechanisms. Thus, the pharmacological activities and applications of CTS have extensive prospects, which would provide a direction for new drug research and development. Here, we review the potential applications of CTS in cardiovascular system and other systems. We also provide suggestions for new clinical practical strategies of CTS, for many diseases. Four main themes will be discussed, in relation to the impact of CTS, on 1) tumors, 2) viral infections, 3) nervous system diseases and 4) immune-inflammation-related diseases.